Enhanced Security of Public Integrity Auditing for Outsourced Data in Cloud Storage - Verma, Deepak Kumar; Verma, Rajesh Kumar; Chaudhary, Vikas (International Journal of Advanced Science and Technology, 2019)
Cloud storage is now being used for storing all types of data like financial, medical, legal, technical, etc. and offers significant benefits over local storage. In addition, data access needs to be controlled and regularly audited to prevent unlawful access. The objective of this paper is to offer a secure and efficient public integrity auditing method for dynamic data in a cloud storage with dynamic data operations. In this scheme, the file-sharing and dynamic operations like append, insert, delete, and update uses algebraic signature properties. To minimize the auditing cost, an index table has been used with less difficult operations in contrast to bilinear pairing. This is poised to incur minimum computation overhead at the data owner side. Finally, the performance evaluation shows that the proposed scheme is more secure and efficient in comparison to other presented schemes.